Self-efficacy as moderator in relationship between individual, environmental, and cognitive factors and cigarette smoking behavior among adolescents in Kerman, Iran - Golestan, Samira (2014)
The main objective of this study was to examine the relationship between personality traits (extraversion, neuroticism, agreeableness, conscientiousness, and openness), environmental factors (family smoking, peer pressure, family cohesion and adaptability) and the cognitive factor of stress on cigarette smoking behavior. In addition, this study intended to determine the moderating effects of self-efficacy on the relationship between personality traits (extraversion, neuroticism, agreeableness, openness, and conscientiousness), environmental factors (family smoking, peer pressure, family cohesion and adaptability) and the cognitive factor of stress and cigarette smoking behavior and also to identify which variable significantly predict cigarette smoking behavior among adolescent in Kerman-Iran. A quantitative research method was employed. The samples included three hundred current smoker adolescents between the ages of 15 to 18. The data collected by means of self-administered questionnaires and then analyzed by AMOS software (to run SEM) for windows program version 20. The result showed that there were significant relationships between personality traits (neuroticism and conscientiousness) and cigarette smoking behavior whereas there were no significant relationships between personality traits (extraversion, agreeableness and openness) and cigarette smoking behavior. Also, positive significant relationship between environmental factors (family smoking and peer pressure) and negative significant relationships between environmental factors (family cohesion and family adaptability) and cigarette smoking behavior were observed. Moreover, there were significant positive relationships between cognitive factor; i.e. stress and cigarette smoking behavior. The result showed that the independent variables; i.e. personality traits (extraversion, neuroticism, agreeableness, openness, and conscientiousness), environmental factors (family smoking, peer pressure, family cohesion and adaptability) and the cognitive factor of stress, explain 77% of variation for dependent variable of cigarette smoking behavior and based on standardized regression weight the independent variable of peer pressure, with highest standardized regression weight (β = .222) among other independent variables, had a highest contribution to explain the variation of cigarette smoking behavior among the respondent. The results related to the moderating effect of self-efficacy revealed that self-efficacy significantly moderated the effect of neuroticism as a personality trait on cigarette smoking behavior but did not moderate the relationship between other personality traits i.e. extraversion, openness, agreeableness and conscientiousness with cigarette smoking behavior. Also, the results showed that self-efficacy significantly moderated the relationship between cigarette smoking behavior and all environmental factors (including family smoking, peer pressure, family cohesion and family adaptability) and the cognitive factor of stress. These findings were supported by relevant theories and were also consistent with the previous studies. The findings of this study can contribute to the literature and has noteworthy implications for practitioner and policy makers to prevent cigarette smoking behavior among adolescents in Iran. Therefore, it is recommended that, future prevention interventions programs focus on reducing cigarette smoking behavior among adolescents by enhancing family awareness, stress management, refusal skills to resist environmental pressure to smoke, enforcing family policies on smoking, enhancing self-efficacy and life skills, and also educating adolescents on how to behave in a smoking group and how to refuse the environmental temptations. So, families, schools and policy makers influence the cigarette smoking behavior and can reduce the level of cigarette smoking among adolescents by devising and implementing a comprehensive program.